Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.